Identification of water production mechanisms utilizing an array of analytical diagnostic techniques: A case study in a Yemeni oilfield - Ebrahim S. Bin Marta; Mohamed M. Soliman; Mohamed A. Khamis; Ali M. Wahba (Water Cycle, 2025)
Excessive water production (EWP) poses a complicated challenge for the oil and gas sector. Even after treatment, this water may contain harmful components impacting the economy, environment, and human health. Therefore, it is crucial to identify the reasons for EWP to minimize or prevent it. This can be achieved by utilizing various techniques, including well testing, well logging techniques, reservoir modeling, and analytical approaches. This research focused on a suite of diagnostic plots—X-plots, Chan's plots, and traditional water cut vs. time linear plot techniques—which are recognized as the simplest, most cost-effective techniques for identifying water production mechanisms. The study's findings confirmed the presence of water production issues in all the wells under investigation. Traditional water cut vs. time linear plots indicate that water coning is the major mechanism of excessive production in all wells except for two wells, indicating near-wellbore water channeling and the presence of high conductive zones. Conversely, Chan's plots suggested that the main mechanism is multilayer channeling through fractures and/or high-permeability zones except for two wells, which exhibit near-wellbore water channeling. These results are further supported by X-plot analysis, which revealed that two of the four selected wells have a layering system, while the other wells exhibit a linear slope or no layering system. Over 110 million barrels of water have been produced, posing a significant environmental challenge due to the potential for substantial pollution. Treating this large volume of water is costly; thus, implementing a water flooding program to reinject the produced water into the reservoir is strongly recommended.